Characterization of Pseudofusicoccum Species from Diseased Plantation-Grown Acacia mangium, Eucalyptus spp., and Pinus massoniana in Southern China - Guoqing Li; Wenxia Wu; Linqin Lu; Bingyin Chen; Shuaifei Chen (Pathogens, 2023)
Fungi from Pseudofusicoccum (Phyllostictaceae, Botryosphaeriales) have been reported as pathogens, endophytes, or saprophytes from various woody plants in different countries. Recently, Botryosphaeriales isolates were obtained from the dead twigs of Acacia mangium, Eucalyptus spp., Pinus massoniana, and Cunninghamia lanceolata in Guangdong, Guangxi, Hainan, and Fujian Provinces in southern China. This study aimed to understand the diversity, distribution, and virulence of these Pseudofusicoccum species on these trees. A total of 126 Pseudofusicoccum isolates were obtained, and the incidences of Pseudofusicoccum (percentage of trees that yielded Pseudofusicoccum) on A. mangium, P. massoniana, Eucalyptus spp., and C. lanceolata were 21%, 2.6%, 0.5%, and 0%, respectively. Based on the internal transcribed spacer (ITS), translation elongation factor 1-alpha (tef1), and β-tubulin (tub2) loci, 75% of the total isolates were identified as P. kimberleyense, and the remaining isolates were identified as P. violaceum. For P. kimberleyense, the majority of isolates (83%) were from A. mangium, and the rest were from P. massoniana (14%) and Eucalyptus spp. (3%). Similarly, the proportion of isolates of P. violaceum from A. mangium, P. massoniana, and Eucalyptus spp. were 84%, 13%, and 3%, respectively. Inoculation trials showed that the two species produced expected lesions on the tested seedlings of A. mangium, E. urophylla × E. grandis, and P. elliottii. This study provides fundamental information on Pseudofusicoccum associated with diseases in main plantations in southern China.